On Place Safety - Kauko Tom (Real Estate Management and Valuation, 2022)
For a long time, social factors have been identified as a set of crucial determinants of residential location choice and property value. Here, safety and security issues constitute a significant issue. Inhabitants are traditionally concerned about their neighborhoods and housing locations, and, considering current problems in big Western cities, this concern is by no means lessening. The study presents a social innovation for assisting the search for safe housing environments. A list of quantifiable key features regarding negative externalities and actual criminality provides the basis for constructing a checklist for the comparison of safe places within a city, or comparing cities with respect to their safety for housing occupants, investors, developers and other stakeholders. The controversial nature of the argumentation notwithstanding, this method is suggested to prove valuable in circumstances marred by increasing social hazards and turmoil.